Translation ideology of cultural words used in the translation of Okky Madasari's kerumunan terakhir into the last crowd - Nur Rahimah Latifah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2018)
wt,1./ws.c.1